Management Strategies to Adapt Alpine Space Forests to Climate Change Risks - Ann Cerbu, Gillian; Hanewinkel, Marc; Gerosa, Giacomo; Jandl, Robert (IntechOpen, 2013)
Climate scenarios suggest that current forest stands will face radically different temperature and precipitation conditions in the future. Developing future strategies for forest management in the face of uncertain and highly variable forecasts of future site conditions is a great challenge. Here we have analyzed transnational case studies dealing with different manifestations of climate change effects. We intend to stimulate the discussion on management strategies to adapt forests in the Alps to climate change risks. The presented results are derived from the INTERREG project "Management Strategies to Adapt Alpine Space Forests to Climate Change Risks" that was implemented within the framework of the European Territorial Cooperation "Alpine Space Programme" 2007-2013.